Analisis Kinerja Berth Time Kapal Kargo Muatan Curah Kering dan Usulan Perbaikannya di Terminal Jamrud Pelabuhan Tanjung Perak Surabaya - Puspandam Katias; Iyori Kharisma Muhammad (UNUSA Press, 2017)
This study aims to analyze berth time performance of ship cargo carrying dry bulk at Jamrud Terminal Port of Tanjung Perak Surabaya, particularly performance which related to effectively and efficiency. Berth time performance was analyzed using productivity (ton/gank/hour) and effective time: berth time (ET:BT). This study also identify factors affecting berth time performance using interview and observation with informants whom understand and involved in berth time process of dry bulk ship cargo, and the factors grouped into 5 category: man, machine & facility, process, environment, and material, and will be explained further using cause and effect diagram. The analysis shows that the average of productivity performance (T/G/H) is 165, far above the given standard which is 125, though some activities are still below. While the average performance of ET:BT only reach 54%, still below standard given which is 70%, and none of them even reach 90% of standard given. From the interview and discussion with the informants shows that the main cause of this unachieved berth time performance standards is the long shift that labors been through.